Thickness dependence on superconducting and structural properties of thin fese0,5te0,5 films (2012)
In the present work the influence of the layer thickness of FeSe0,5Te0,5 on the crystalline and superconducting properties of films deposited on iron (Fe) buffered MgAl2O4 substrates by pulsed laser deposition (PLD) is investigated. The superconducting layer thicknesses of the films prepared are ~55nm and ~134nm. The film with thinner superconducting layer shows better texture properties (oriented growth) and lower surface roughness (RMS); verified by X ray diffraction and AFM respectively. This film shows a sharp transition to the superconducting state and a higher critical temperature in contradiction to the thicker one. The thickness effect on superconducting lattice strain is discussed.